2020
DOI: 10.1039/c9py01348b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and stereochemistry of helical polyurethanes based on 2,2′-dihydroxy-1,1′-binaphthyl and diisocyanatobenzenes

Abstract: Helical polyurethanes were prepared from 1,4- and 1,3-diisocyanatobenzene and BINOL having various e.e.'s where helix handedness was governed by absolute configuration of major enantiomer of BINOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The polymer is well soluble in common organic solvents, and the stacked structure can be made disordered by adding a hydrogen‐bond‐competitive reagent, DMSO. The presented novel π‐stacked architecture cannot be synthesized using conventional organic synthesis and polymerization, and this 2 1 ‐helical conformation has only been known for limited types of polymers and some polydienes in the solid state . Additionally, this polymer is prepared by living polymerization of 1 , and further modifications of the molecular design, such as the monomer sequence and end‐structure, are possible.…”
Section: Figurementioning
confidence: 99%
“…The polymer is well soluble in common organic solvents, and the stacked structure can be made disordered by adding a hydrogen‐bond‐competitive reagent, DMSO. The presented novel π‐stacked architecture cannot be synthesized using conventional organic synthesis and polymerization, and this 2 1 ‐helical conformation has only been known for limited types of polymers and some polydienes in the solid state . Additionally, this polymer is prepared by living polymerization of 1 , and further modifications of the molecular design, such as the monomer sequence and end‐structure, are possible.…”
Section: Figurementioning
confidence: 99%
“…The CD signal at 260 nm was attributed to the chirality inherent of the S-BINOL unit. [34,51,52] Notably, the CD and UV-vis absorption spectra were carried out on S-PUEs 9 film under varying geometric testing angles (0°, 90°, 180°, 270°) to verify the reliability of the data, as shown in Figure S5a (Supporting Information). [53] The analyses confirmed that the line shape and intensity of CD signals from different angles were almost identical.…”
Section: Figure S4 (Supporting Informationmentioning
confidence: 99%
“…[29,30] Chiral supramolecular polyurethanes with ordered hard segments and helical conformation have been further fabricated, which combines the respective advantages of helical polymers and elastomers. [31][32][33][34] Nakano et al reported the synthesis of a chiral polyurethane from optically active (R)−1,1′-bi(2-naphthol) (R-BINOL) and 1,4 phenylene diisocyanate. [32] While Hayes et al synthesized a series of novel supramolecular polyurethanes elastomers that feature chiral polar end-groups and investigated how highly oriented stereochemistry enhanced the phase separated structures and the mechanical properties of polyurethane.…”
Section: Introductionmentioning
confidence: 99%
“…2,2′‐Dihydroxy‐1,1′‐binaphthyl or 1,1′‐bi‐2‐naphthol ( BINOL ) has an excellent chiral backbone based on the 1,1′‐binaphthyl group which has been used as a structural motif of chiral materials including small molecules and polymers 1–9 . The axial chirality around the single bond connecting the two naphthyl groups creates effectively twisted asymmetric structure which is suitable for chiral recognition, chiral catalysis, and circularly polarized light emission.…”
Section: Introductionmentioning
confidence: 99%
“…2,2 0 -Dihydroxy-1,1 0 -binaphthyl or 1,1 0 -bi-2-naphthol (BINOL) has an excellent chiral backbone based on the 1,1 0 -binaphthyl group which has been used as a structural motif of chiral materials including small molecules and polymers. [1][2][3][4][5][6][7][8][9] The axial chirality around the single bond connecting the two naphthyl groups creates effectively twisted asymmetric structure which is suitable for chiral recognition, chiral catalysis, and circularly polarized light emission. One of the most renowned applications of 1,1 0 -binaphthyl group is 2,2 0 -bis (diphenylphosphino)-1,1 0 -binaphthyl (BINAP), a highly effective chiral ligand used in combination with Ru for asymmetric hydrogenation.…”
Section: Introductionmentioning
confidence: 99%